2016
DOI: 10.1210/jc.2015-2175
|View full text |Cite
|
Sign up to set email alerts
|

Global Consensus Recommendations on Prevention and Management of Nutritional Rickets

Abstract: Rickets, osteomalacia, and vitamin D and calcium deficiencies are preventable global public health problems in infants, children, and adolescents. Implementation of international rickets prevention programs, including supplementation and food fortification, is urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
803
1
55

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 882 publications
(872 citation statements)
references
References 233 publications
13
803
1
55
Order By: Relevance
“…Another important factor is the dependence on clinical signs such as lower limb deformities for the diagnosis of rickets. The recent Global Consensus guidelines on Nutritional Rickets 1 recommended that the diagnosis is made on the basis of history,physical examination and biochemical results and is confirmed by radiographs. It is recognized that access to such investigations may be difficult in countries such as Kenya but it would have been useful if radiographs were available in a subset of the sample to see what proportion of cases of rickets were confirmed on X-ray.…”
mentioning
confidence: 99%
“…Another important factor is the dependence on clinical signs such as lower limb deformities for the diagnosis of rickets. The recent Global Consensus guidelines on Nutritional Rickets 1 recommended that the diagnosis is made on the basis of history,physical examination and biochemical results and is confirmed by radiographs. It is recognized that access to such investigations may be difficult in countries such as Kenya but it would have been useful if radiographs were available in a subset of the sample to see what proportion of cases of rickets were confirmed on X-ray.…”
mentioning
confidence: 99%
“…As shown in numerous epidemiological studies, vitamin D insufficiency is found in almost half of the world's population [4,5,19], including children, because the most active bone growth and mineralization processes occur during childhood and pubescence [6,7,14]. It has been shown; in particular, that 30 % to 50 % of the population residing in Europe and the United States have vitamin D insufficiency [17].…”
mentioning
confidence: 99%
“…Vitamin D deficiency is partially compensated (i. e. the 25(OH)D concentration increases to >30 ng/mL) and no hypercalcaemia occurs in children and adolescents given such doses for 6 months. 25(OH)D concentrations of 30 ng/mL or higher are required for manifestation of the extraskeletal effects of vitamin D. Additionally, the upper limit for serum calcifediol was established (30-50 ng/ mL or 75-125 nmol/L) at which a switch to prophylactic cholecalciferol supplementation is recommended, because any levels of calcifediol above 50 ng/mL are considered by the authors to be a «high concentration necessitating a decrease of the therapeutic dose» [14,18,20,22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been a number of international initiatives to address these issues. [1] At the beginning of this year, a consensus group comprising representatives from paediatric endocrine societies, nutrition societies and individual experts published a consensus statement on the prevention and management of nutritional rickets in the Journal of Clinical Endocrinology and Metabolism [2] and Hormone Research in Paediatrics. [3] This consensus statement was the culmination of a review of the literature by five task teams and a three-day workshop held in 2014.…”
mentioning
confidence: 99%